(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to determine the extent to which the social image of the physical education teacher affects their job performance and to identify the most important aspects surrounding the physical education teacher that may influence their performance. Teaching is a demanding profession with many variables. The teacher’s role is not limited to simply preparing and implementing the teaching process, but extends to the necessity of keeping up with various scientific and technological developments and being familiar with the latest methods and techniques. The current study derives its importance from the concept it examines: the social image of the physical education teacher and its influence on society, to the extent that it contributes positively or negatively to their job performance, ultimately leading to the development of the individual’s personality in order to create a generation capable of contributing to the educational development of society. The study concluded that the teacher enjoys appreciation and respect in society, which reflects the culture and development of the society, and that the teacher is viewed as having a mission and an active role in building society.